2020
DOI: 10.1007/s10637-020-00912-7
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective review of the activity and safety of apatinib and anlotinib in patients with advanced osteosarcoma and soft tissue sarcoma

Abstract: Summary Background Previous studies have demonstrated the efficacy of apatinib and anlotinib for the treatment of sarcomas. However, more clinical data and evidence are needed to support clinical treatment selection and study design. Here, we evaluated the effectiveness and safety of these two drugs for the treatment of sarcomas. Methods We retrospectively reviewed the data of 110 patients with advanced osteosarcoma (n = 32) or soft tissue sarcoma (STS, n = 78) who received oral apatinib or anlotinib therapy d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
42
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 41 publications
(50 citation statements)
references
References 30 publications
7
42
1
Order By: Relevance
“…To our knowledge, this study is the rst to focus on pneumothorax in osteosarcoma patients treated with apatinib. The results of this study showed that the incidence of pneumothorax in osteosarcoma patients treated with apatinib was 25.93%, which was similar to previous reports [5,11,12]. However, the incidence of pneumothorax in osteosarcoma patients treated with sorafenib and regorafenib, the other two multitarget TKIs that have been shown to be effective in osteosarcoma treatment, was 3% and 0%, respectively [4,6,7].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…To our knowledge, this study is the rst to focus on pneumothorax in osteosarcoma patients treated with apatinib. The results of this study showed that the incidence of pneumothorax in osteosarcoma patients treated with apatinib was 25.93%, which was similar to previous reports [5,11,12]. However, the incidence of pneumothorax in osteosarcoma patients treated with sorafenib and regorafenib, the other two multitarget TKIs that have been shown to be effective in osteosarcoma treatment, was 3% and 0%, respectively [4,6,7].…”
Section: Discussionsupporting
confidence: 87%
“…As a multitarget TKI marketed for the treatment of advanced or metastatic gastric cancer in China, apatinib has been shown to be effective for the treatment of osteosarcoma. In our previous work, we found that the incidence of pneumothorax in patients with osteosarcoma treated with apatinib was 18.18%-31.58% [10,11]. which was similar to the results of other studies [5,12].…”
Section: Introductionsupporting
confidence: 90%
“…Another clinical implication of this finding is that the systemic therapeutic effect of anlotinib cannot substitute for the therapeutic effect of radiotherapy in local treatment. This result has also been confirmed by numerous clinical trials 13–15 …”
Section: Discussionsupporting
confidence: 69%
“…As a major sarcoma treatment center in central China, our institution has used high cumulative doses of doxorubicin in our clinical work to treat a number of patients with advanced STS, because of the lack of other effective treatment modalities [ 18 ]. In this study, we aimed to review and analyze the clinical data of these patients to provide a reference for treatment selection and clinical trial design for treating advanced STS.…”
Section: Introductionmentioning
confidence: 99%